2018
DOI: 10.1007/s10071-018-1202-2
|View full text |Cite
|
Sign up to set email alerts
|

Opposing pupil responses to offered and anticipated reward values

Abstract: Previous studies have shown that the pupils dilate more in anticipation of larger rewards. This finding raises the possibility of a more general association between reward amount and pupil size. We tested this idea by characterizing macaque pupil responses to offered rewards during evaluation and comparison in a binary choice task. To control attention, we made use of a design in which offers occurred in sequence. By looking at pupil responses after choice but before reward, we confirmed the previously observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…This assumption is reasonable because several carefully conducted experiments have shown that pupil size scales with emotional arousal [37] and the value of primary reinforcement [36,38]. However, pupillary responses are complex [39], pupil size is affected by factors other than anticipated value [40,41], and even reliable value-related pupil changes are more nuanced than a simple model in which high anticipated value always produces large pupils [42]. Indeed, our own measures of pupil response during vicarious reinforcement demonstrate some of this nuance [30].…”
Section: Plos Biologymentioning
confidence: 99%
“…This assumption is reasonable because several carefully conducted experiments have shown that pupil size scales with emotional arousal [37] and the value of primary reinforcement [36,38]. However, pupillary responses are complex [39], pupil size is affected by factors other than anticipated value [40,41], and even reliable value-related pupil changes are more nuanced than a simple model in which high anticipated value always produces large pupils [42]. Indeed, our own measures of pupil response during vicarious reinforcement demonstrate some of this nuance [30].…”
Section: Plos Biologymentioning
confidence: 99%
“…Although we did not directly ask participants to rate their arousal in response to the stimuli, pupil sizes have been repeatedly used as its proxy [ 27 ]. However, this selective interpretation stands in contrast to the growing body of literature utilising pupillometry in reward research (e.g., [ 28 , 29 , 30 , 31 , 32 ]). Moreover, if the negative relationship of pupil sizes and familiarity in our study was indeed a reflection of reduced arousal to more familiar faces, this contradicts previous reports of familiar faces (especially with happy expressions) judged as more arousing than unknown ones [ 36 ].…”
Section: Discussionmentioning
confidence: 71%
“…The pupil systematically dilates in response to mental processes, such as cognitive activity, mental effort, or increasing levels of arousal [ 27 ]. Importantly, the increase in its size has been linked to goal-priming with rewards [ 28 ], to higher magnitude of possible rewards [ 29 ], and to reward anticipation [ 30 , 31 ]. Similarly, pleasant (and rewarding) images of smoking-related cues trigger an increase in smokers’ pupil sizes [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the pupillary response has been shown to be modulated by probabilities and at least qualitatively demonstrates more extended responses to low probability events ( Alamia et al, 2019 ; Qiyuan et al, 1985 ; Zénon, 2019 ), we cannot completely rule out this possibility. Nor can we rule out the possibility that the difference between explore and exploit response was due to anticipated outcome, which prior studies have demonstrated positively modulates pupil diameter ( Cash-Padgett et al, 2018 ; Van Slooten et al, 2018 ; Varazzani et al, 2015 ). In this task, we cannot decouple outcome anticipation from outcome uncertainty due to the constrained nature of value changes in this task.…”
Section: Discussionmentioning
confidence: 98%